Determination of the Biological Activity of Heparin by Use of a Chromogenic Substrate - Bartl, Knut; Dorsch, Elfriede; Lill, Helmut; Ziegenhorn, Joachim (Thrombosis and Haemostasis, 1979)
We describe a new method for determining the biological activity of heparin in plasma with use of thrombin and the substrate Tos-Gly-Pro-Arg-pNA. The procedure is based on the photometric determination of the inactivation of thrombin after incubation with plasma in the presence of endogenous antithrombin III (At III). The method allows the specific determination of heparin concentrations from 0.02 USP to 0.8 USP/ml of plasma in the presence of normal At III levels. It has been carried out manually by use of an Eppendorf spectrum line photometer or automatically by use of a Vitatron Akes analyzer. For evaluation, the results were compared with two standard samples which contained heparin in the low and high therapeutic range, respectively.